2023
DOI: 10.3390/cryst13071123
|View full text |Cite
|
Sign up to set email alerts
|

Layered Epitaxial Growth of 3C/4H Silicon Carbide Confined by Surface Micro-Nano Steps

Abstract: In this study, we used a horizontal hot-wall CVD epitaxy apparatus to grow epitaxial layers on 4° off-axis 4H-SiC substrates. Epitaxial films were grown by adjusting the flow rate of the source gas at different levels. With an increase in the source gas flow rate, a notable transition in the crystalline structure of the epitaxial layer was observed, gradually shifting from 4H-SiC to 3C-SiC. Furthermore, the quality of the epitaxial layer correspondingly exhibited degradation. Specifically, for epitaxial films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 3,4 Previous research has shown that under conditions of significant fluctuations in source gas flow rates during epitaxial growth, especially when the magnitude of the flow rate variation is nearly equal to the magnitude of the source gas flow rate itself, there is a gradual transition of the epitaxial growth from 4H to 3C polytype as the source gas flow rate increases. 5 Under specific source gas flow rate conditions, both 3C and 4H polytypes may simultaneously appear on the same epitaxial wafer. In order to determine the influence of source gas flow rates on homoepitaxial growth of 4H-SiC during homoepitaxial growth, and to provide better references for controlling the growth parameters of homoepitaxial 4H-SiC processes, it is necessary to vary experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 3,4 Previous research has shown that under conditions of significant fluctuations in source gas flow rates during epitaxial growth, especially when the magnitude of the flow rate variation is nearly equal to the magnitude of the source gas flow rate itself, there is a gradual transition of the epitaxial growth from 4H to 3C polytype as the source gas flow rate increases. 5 Under specific source gas flow rate conditions, both 3C and 4H polytypes may simultaneously appear on the same epitaxial wafer. In order to determine the influence of source gas flow rates on homoepitaxial growth of 4H-SiC during homoepitaxial growth, and to provide better references for controlling the growth parameters of homoepitaxial 4H-SiC processes, it is necessary to vary experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 200 mm diameter SiC single crystal substrate is still in the early stage of industrialization, and there is still a significant gap in crystal quality and thickness compared to 6-inch SiC. For decades, people have adopted many methods to improve crystal quality and size [8][9][10], including using seed crystals with a certain angle to better meet the requirements of step flow growth mode and reduce the number of defects, using different seed crystal fixation methods to reduce stress caused by different thermal expansion coefficients between materials and graphite [11,12], and adopting different materials and structures to optimize the internal environment of the chamber [13][14][15]. Some researchers studied dislocation formation and found that the largest dislocation density is focused near the graphite and SiC interface [16].…”
Section: Introductionmentioning
confidence: 99%